Application of Student Satisfaction Levels with Academic Information Systems Through the Six Sigma Method Approach (Case Study: Accounting Study Program, Faculty of Economics, Unived Bengkulu) - Rahmad Arfandi; Maryaningsih Maryaningsih; Prahasti Prahasti (GATOTKACA Journal (Teknik Sipil, Informatika, Mesin dan Arsitektur), 2021)
This study aims to build an Application of Student Satisfaction Levels with Academic Information Systems Through the Six Sigma Method Approach in the Accounting Study Program, Faculty of Economics, Unived Bengkulu, which becomes a measure of quality that moves towards perfection through statistical testing. With this application, it can be used to find information on the level of student satisfaction and evaluate the satisfaction assessment given by each student to the Unived Bengkulu Academic Information System. Based on the tests that have been carried out on 98 respondents with a 95% confidence level and a margin of error value of 10%, it can be concluded that the level of satisfaction received by students is in expressing satisfaction even though there are indicators that need to be improved or improved. The statistical test results of the validity test on 23 questions were declared valid, the reliability test was 0.99957, the stability test with the lower control limit was -0.4047 and the DPMO results obtained that the minimum value was found in P5 with a DPMO value of 0 which indicates the highest level of satisfaction and the maximum value. at P8 and P17 with a DPMO value of 200000 which shows the lowest level of satisfaction.